Utilization of the Canadian Incidence Study of Reported Child Abuse and Neglect in First Nations Child Welfare Agencies in Ontario - Tonmyr, Lil; Jack, Susan; Brooks, Sandy; Kennedy, Betty; Dudding, Peter (First Peoples Child & Family Review, 2009)
The goals of this study are: to examine the awareness and utilization of the Canadian Incidence Study of Reported Child Abuse and Neglect (CIS) and the Ontario Incidence Study of Reported Child Abuse and Neglect (OIS) by First Nations child welfare decision-makers in the child welfare policy development process in the Province of Ontario and; to identify ways of making the CIS/OIS more useful to First Nations decision makers. No previous study has focused on assessing the inﬂuence and impact that the CIS/OIS data have on policy development with this speciﬁc population.